Development Of Motion Planer And Navigation System For An Office Assistant Robot - Looi, Chen Zheng (2021)
In the past decades, service robot industry had rise rapidly. There are many types of service robot used in different field such as medical. Office assistant robot is one type of the service robot used to assist officers. The robot used in this research is a differential drive robot. In order for the robot to navigate autonomously in the office, navigation algorithm and motion planner were implemented on these robot. Robot Operating System (ROS) is one of the common platforms to developed these robots. Besides, map was generated by using SLAM algorithm, the costmap was setup and the parameters such as inflation_dist and cost_scaling_factor was studied and tuned based on this application. Next, the localization of robot was based on the LiDAR sensor and rotary encoder with AMCL algorithm. In this research the global planners, A* and Dijkstra algorithm and local planners, DWA and TEB algorithms were implemented and tested on the robot in in simulation and a real environment. Results from the experiments were used to evaluate and compare the performance of the robot with different planner and parameters. From the results obtained, the global planners, A* and Dijkstra algorithm both can achieve the required performance for this application whereas TEB outperforms DWA as the local planner due to its feasibility in avoiding dynamic obstacles in the experiments conducted.